Effects of Neurostimulation on Poststroke Dysphagia: A Synthesis of Current Evidence From Randomized Controlled Trials. Issue 8 (10th December 2020) - Cheng, Ivy; Sasegbon, Ayodele; Hamdy, Shaheen
Abstract: Objectives: To evaluate the effects of neurostimulation, including repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS) and pharyngeal electrical stimulation (PES), for poststroke dysphagia based on evidence from randomized controlled trials (RCTs). Materials and Methods: Electronic databases were systematically searched between January 1985 and June 2020 and studies were included based on prespecified selection criteria. The quality of studies was evaluated and data were extracted and synthesized by two independent reviewers. The primary outcome measure was change in (any) relevant clinical swallowing‐related characteristic. Subgroup analysis were conducted based on follow‐up period and stimulation parameters. Results: Data from 852 stroke patients were collected from 26 RCTs studies. Active neurostimulation treatments demonstrated a significant and moderate effect size compared to control treatment (0.69 [95% CI = 0.50, 0.89]; p < 0.001). The effect size of rTMS was the largest (0.73 [95% CI = 0.49, 0.98]; p < 0.001), followed by PES (0.68 [95% CI = 0.22, 1.14]; p = 0.004) and tDCS (0.65 [95% CI = 0.25, 1.04]; p = 0.001). All treatments showed comparable effect sizes within the first two weeks. Between three weeks and two months, tDCS demonstrated the largest effects (1.02 [95% CI = 0.45, 1.59]; p < 0.001) among the three treatments. No significant treatment effects were reported beyond three months. The combined effect size was large when applied in acute (<14 days) stroke (0.8 [95% CI = 0.34, 1.26]; p < 0.001). For noninvasive brain stimulation (NIBS), bihemispheric stimulation demonstrated the strongest effect size (0.93 [95% CI = 0.53, 1.33]; p < 0.001). In contrast, unilateral rTMS using ipsilesional high‐frequency stimulation had a combined effect size of 0.83 (95% CI = 0.14, 1.52; p = 0.02). For tDCS, a significant effect size was found only with anodal stimulation applied over the contralesional hemisphere (1.04 [95% CI = 0.54, 1.53]; p < 0.001). Conclusions: The results show that neurostimulation can benefit patients with poststroke dysphagia. The treatment effects were the strongest in acute stroke patients and within the first two months of application. For NIBS, bihemispheric stimulation appeared to be most effective. The most beneficial hemisphere for unilateral stimulation differed between rTMS and tDCS. These findings provide a platform for future studies and clinical practice.